A realization model to develop the autopilot system of ships by specializing MDA - Ngo Van Hien; Vu Duy Quang (Vietnam Journal of Mechanics)
This paper presents a method which is based on the Model-Driven Architecture (MDA) and functional blocks to realize effectively the autopilot systems of ships. It brings out an executable MDA process to cover completely the requirement analysis, design and deployment phases of these systems. This process also allows the determined design elements to be customizable and re-usable in the new applications of controlled ship steering systems. The paper indicates straightforwardly the ship dynamic model-to-be used, the Computation Independent Model (CIM) of a ship autopilot system, the Platform Independent Model (PIM) of this system by using the Real-Time Unified Modeling Language (UML), and its Platform Specific Model (PSM) implemented by the functional blocks. Furthermore, the important transformation rules are also brought out and applied to convert the identified PIM into PSM for implementing quickly this system with different industrial frameworks such as the IEC61499 in a programmable controller. Then, its deployment model completely is tested on a model ship with the predetermined program and control performance.